2017
DOI: 10.1007/s11120-017-0454-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of the excitation decay in Photosystem I immobilized on glass surface

Abstract: Femtosecond transient absorption was used to study excitation decay in monomeric and trimeric cyanobacterial Photosystem I (PSI) being prepared in three states: (1) in aqueous solution, (2) deposited and dried on glass surface (either conducting or non-conducting), and (3) deposited on glass (conducting) surface but being in contact with aqueous solvent. The main goal of this contribution was to determine the reason of the acceleration of the excitation decay in dried PSI deposited on the conducting surface re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Cyanobacterial PSI immobilized directly on FTO conducting glass has recently been shown by ultrafast optical spectroscopy to preserve excitation quenching properties very similar to those of the native PSI in solution (Szewczyk et al 2017(Szewczyk et al , 2018. The detailed analysis has shown that the observed modest acceleration of the excitation decay in immobilized PSI (by a few ps) may be assigned to the crowding effect similar to that reported for aggregated LHCII (Ruban et al 2007).…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Cyanobacterial PSI immobilized directly on FTO conducting glass has recently been shown by ultrafast optical spectroscopy to preserve excitation quenching properties very similar to those of the native PSI in solution (Szewczyk et al 2017(Szewczyk et al , 2018. The detailed analysis has shown that the observed modest acceleration of the excitation decay in immobilized PSI (by a few ps) may be assigned to the crowding effect similar to that reported for aggregated LHCII (Ruban et al 2007).…”
Section: Introductionmentioning
confidence: 53%
“…In the following, we present photovoltaic data obtained from the system containing simple PSI-FTO photoelectrode identical to that one described in Szewczyk et al (2017Szewczyk et al ( , 2018 and propose a mechanism of the anodic and cathodic photocurrent generation in this system. The advantage of this system is the functionality of immobilized PSI proven to be highly intact at the level of excitation decay and charge separation.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is worth noting that the acceleration of the primary electron transfer reactions as the temperature is decreased was previously observed in bacterial reaction centers (Fleming et al 1988;Kirmaier and Holten 1990;Jia et al 1993). Interestingly, significant acceleration of excitation trapping by RCs was also observed after immobilization of cyanobacterial PSI on conducting glass at RT (Szewczyk et al 2017a, b) and this effect was explained by the dense packing of proteins in the solid-state phase (Szewczyk et al 2017a).…”
Section: Fast Trapping At Low Temperaturesmentioning
confidence: 72%